The effect of calcium addition on fruit chemical composition of some tomato cultivars grown under salt stress - Murshed, Ramzi; Najla, Safaa (Latakia University Journal -Biological Sciences Series, 2013)
A salt stress was applied from 3rd leaf stage until the maturation on three tomato cultivars (Marmara, Levovil and Picolino). The salt stress was achieved by increasing the solution EC from 3 (control) to 6.7 dS/m for, Na and Na+Ca treatments, respectively. The stress induced a significant increase in vitamin C of Marmara and Levovil fruit content (20.94 and 23.03 mg/100g) as compared to the control (16.62 and 19.43 mg/100g, respectively). The titratable acidity was increased significantly (17%) only in Marmara and Picolino. The fruit content of fructose was increased in Levovil and Picolino by 1.4 and 1.7 folds, respectively, as compared to control (11.13 and 18.8g/kg, respectively). While the content of N in Levovil and Picolino was decreased, under stress, by 33 and 58% as compared to the control (0.12 and 0.19%), respectively, the P content was increased. The salt stress decreased the K content in Levovil and Picolino to reach to 0.22 and 0.26% as compared to control (0.27 and 0.29%), respectively. The calcium addition modified the stress impact. A significant increase, was registered in Ca content under stress in Marmara andPicolino as compared to control, while the calcium addition did have any effect on.